1960
DOI: 10.1152/jappl.1960.15.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in human amino acid excretion

Abstract: Amino acid excretion was studied in young, healthy men during summer, fall and winter months in a southwestern U. S. location. Both untimed and timed urine samples were employed. The amino acids determined were alanine, arginine, cysteine, glutamic acid, glutamine, glycine, histidine, lysine, methyl histidine, serine, threonine and valine. Supplemental determinations included urine volume, creatinine, uric acid, urea, sodium and potassium. Using untimed urine samples and expressing values as ratios with creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
1973
1973

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Turning, finally, to the problem of climatic change as a variable in protracted studies, Wieland and Mefferd (1970) consider some aspects of this, citing Wenger (1943), Wenger and Cullen (1962), Mefferd (1959), and Hale, Ellis, and Van Fossan (1960). Wenger and Cullen (1962) noted that they were unable to replicate, in summer months, psychophysiological findings obtained in temperate periods; Christie and Venables (1971b) reported a similar inability to replicate, in summer months, findings on BSPL and ECG T-wave relationships.…”
Section: Length Of Record Time Of Day and Seasonmentioning
confidence: 99%
“…Turning, finally, to the problem of climatic change as a variable in protracted studies, Wieland and Mefferd (1970) consider some aspects of this, citing Wenger (1943), Wenger and Cullen (1962), Mefferd (1959), and Hale, Ellis, and Van Fossan (1960). Wenger and Cullen (1962) noted that they were unable to replicate, in summer months, psychophysiological findings obtained in temperate periods; Christie and Venables (1971b) reported a similar inability to replicate, in summer months, findings on BSPL and ECG T-wave relationships.…”
Section: Length Of Record Time Of Day and Seasonmentioning
confidence: 99%
“…Thi s'same . summer-autumn variation in the urea creatiOthers "iave studied the effects of acute nine ratio was found in an earlier study (12), heat expo.ýure on the human. Berman et al in which daytime urine, rather than nighttime (15) found no evidence of high c atecholamine urine, was analyzed.…”
Section: Is Being Determined'-"mentioning
confidence: 97%